The Use Word Card Media to Improve Reading Skills of Elementary School Students: A Literature Review - Umi Ningsih; Yasinta Mahendra; Sumarno (Journal for Lesson and Learning Studies, 2025)
Low reading proficiency among elementary school students remains a persistent challenge in early education. This research aims to share empirical evidence regarding the effectiveness of implementing word card media to improve students' reading skills. This media can be an interesting strategy to apply in Indonesian language learning. This research uses the systematic literature review (SLR) technique with a literature review method explaining that SLR or systematic literature review is research used in the field of research and development and also refers to research methodology and also measurements related to focus on a particular topic, research results based on the keyword "use of word card media" from research results using keywords, 145,000 search articles were found, then continued with the limitation period of 2019-2024 which resulted in 1,030 articles were searched by adding the keyword "student reading ability" found 210 articles adding the keyword "primary school" to the search resulting in 191 articles. Of the 191 articles reviewed and selected and evaluated, they were determined worthy of being part of the conclusion analysis. The results showed that the use of word cards Image media can improve elementary school students' reading skills. Therefore, it is recommended to use word card media in elementary schools and can also improve teachers' ability to utilize technology by integrating the use of word card media in learning.